Pencil Cup Deformity, A Typical Radiological Finding in Psoriatic Arthritis (Revista de Medicina Clinica, 2022)
Clinical snapshot on "Pencil Deformity in Cup, Typical Radiological Finding of Psoriatic Arthritis" presented in volume 6 Issue 3 of Revista de Medicina Clínica.
Keywords: Psoriatic arthritis; Arthritis mutilans; Seronegative arthropathies